Effectiveness of lactose-free formula in management of acute rotavirus diarrhea - I. Nyoman Budi Hartawan; S. Yati Soenarto; I. K. G. Suandi (Indonesian Pediatric Society, 2009)
Background Acute rota virus diarrhea causes mucosal destruction, blunted villi, villus shortening, and death of cells. The process also decreases lactose secretion which responsible in lactose absorption. Non-absorbed lactose then causes the progression of osmotic and secretory diarrhea causing delayed recovery. Lactose-free formula may decrease lactose, thus shortened the duration of diarrhea episode.Objective To compare the cure rate and duration of acute rota virus diarrhea in children treated with lactose-free formula and lactose containing formula.Methods A randomized, double-blind controlled trial was performed to infants and children aged 2: 6 to 59 months old with acute rotavirus diarrhea accompanied with mild or moderate dehydration that were admitted to pediatric gastroenterology division. Latex agglutination test was used to detect rota virus. After an appropriate rehydration therapy had been done, they were fed with either lactose-free formula (n = 29) or lactose-containing formula (n = 31). Comparisons between duration of diarrhea, weight gain, and defecation frequency were made. Statistical analysis for comparing the two groups were independent t-test and multivariate analysis (Cox regression). Statistical significant was defined ifF< 0.05 with 95% confidence interval.Results The mean duration of diarrhea in lactose-free formulagroup was 57.59 hours (SD 9.40) and lactose-containing formulawas 85.97 hours (SD 13.94), mean difference was 28.38 hours(SE 3.09) [P = 0.001; (95% CI 22.19 to 34.56)]. Decrease instool frequency was found significantly in the lactose-free formula group. Multivariate analysis (Cox regression) revealed that the intervention was affected significantly.Conclusion Lactose-free formula may shorten the duration of acute rotavirus diarrhea.